A Study on Urbanization and the Associated Challenges (International Journal of Innovative Research in Engineering & Management, 2021)
The concept of urbanisation is the movement of people from  rural to urban regions. It primarily concentrates upon the  construction of towns & cities, as well as the improvement of  more regions in the core region in order to offer housing &  employment for the greatest number of people. It  was investigated the link amongst urbanisation & growth in  the Indian context through evaluating microeconomic  evidence of shared production and infrastructure expenses by  companies and customers, combining more efficiently with  specialised workers and supervisors and learning from other  manufacturers and employees. On the basis of thorough  analysis of urbanisation, there is no effect on urbanism of  urban/rural inequities, but an influence on the population of  the state's biggest city. Taking into consideration the dual  route connection amongst urbanisation & rural-urban income,  it was find that urbanisation initially raises, but at higher  levels it lowers, urban-rural disparities. It was also examines  how rural migration affects metropolitan regions & in what  way urban development helps rural communities. In addition,  conceptual frameworks for telecommute & urban  infrastructure projects are described.
Keywords: Employment; Financial; Industrialization; Metropolitan; Urbanization